2023
DOI: 10.1007/s00784-022-04827-w
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and metabolic effects on the oral status of patients with phenylketonuria: a nation-based cross-sectional study

Abstract: Objectives The aim of this study was to compare the prevalence of oral diseases (caries, periodontal disease, enamel defects) between patients with phenylketonuria (PKU), their siblings, and a matched control group. Materials and methods A total of 109 patients with PKU, 14 siblings of PKU patients, and 100 healthy individuals aged 6 to 68 years were recruited. All participants completed a questionnaire based on their health status. The patients’ decayed/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…PKU patients exhibited worse dental health than controls, which was in part described for this cohort earlier (Bingol et al, 2023), with significantly higher PCR, GBI, PSI and DMFT values, the latter two applying only to the adult group (Table 1). Children with PKU had a significant higher prevalence of DDE than their age‐matched controls and PKU adults.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…PKU patients exhibited worse dental health than controls, which was in part described for this cohort earlier (Bingol et al, 2023), with significantly higher PCR, GBI, PSI and DMFT values, the latter two applying only to the adult group (Table 1). Children with PKU had a significant higher prevalence of DDE than their age‐matched controls and PKU adults.…”
Section: Resultssupporting
confidence: 71%
“…One‐hundred and nine PKU patients, aged 6–68 years, and 114 metabolically healthy age‐matched controls, 15 of whom were siblings of PKU patients from the cohort, were recruited and clinically examined as previously described (Bingol et al, 2023), according to the European guidelines on PKU (van Wegberg et al, 2017). This study followed the Declaration of Helsinki and STROBE protocol (Supplementary Methods) and was approved by the medical ethical committees of the Charité ‐ Universitätsmedizin Berlin (EA2/036/18) and the University of Leipzig (369/18‐Ik), registered in the German Clinical Trials Register and International Clinical Trials Registry Platform (DRKS00027482).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the study limitations, the study findings reported by Ghasemi et al 1 really support the recently published observation that PKU patients have a higher risk to develop DC, enamel defects, and periodontitis. 3 …”
mentioning
confidence: 99%